Anisotropic Properties of Quasi‐1D In4Se3: Mechanical Exfoliation, Electronic Transport, and Polarization‐Dependent Photoresponse. (24th September 2021) - Vorobeva, Nataliia S.; Lipatov, Alexey; Torres, Angel; Dai, Jun; Abourahma, Jehad; Le, Duy; Dhingra, Archit; Gilbert, Simeon J.; Galiy, Pavlo V.; Nenchuk, Taras M.; Muratov, Dmitry S.; Rahman, Talat S.; et al.
Abstract: Theoretical and experimental investigations of various exfoliated samples taken from layered In4 Se3 crystals are performed. In spite of the ionic character of interlayer interactions in In4 Se3 and hence much higher calculated cleavage energies compared to graphite, it is possible to produce few‐nanometer‐thick flakes of In4 Se3 by mechanical exfoliation of its bulk crystals. The In4 Se3 flakes exfoliated on Si/SiO2 have anisotropic electronic properties and exhibit field‐effect electron mobilities of about 50 cm 2  V −1  s −1 at room temperature, which are comparable with other popular transition metal chalcogenide (TMC) electronic materials, such as MoS2 and TiS3 . In4 Se3 devices exhibit a visible range photoresponse on a timescale of less than 30 ms. The photoresponse depends on the polarization of the excitation light consistent with symmetry‐dependent band structure calculations for the most expected ac cleavage plane. These results demonstrate that mechanical exfoliation of layered ionic In4 Se3 crystals is possible, while the fast anisotropic photoresponse makes In4 Se3 a competitive electronic material, in the TMC family, for emerging optoelectronic device applications. Abstract : In4 Se3, a highly anisotropic ionic compound, can be mechanically exfoliated into few‐nanometer‐thick flakes that exhibit field‐effect electron mobilities of about 50 cm 2  V −1  s −1 at room temperature and a visible range photoresponse on a timescale of less than 30 ms, which shows a dependence on the polarization of the excitation light.